PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN KOMUNIKASI DAN BERPIKIR KREATIF PESERTA DIDIK KELAS VII DI MTS DARUL QUR’AN BENGKEL, KABUPATEN LOMBOK BARAT - Lilian Andriani; Suhirman Suhirman; Muhammad Shohibul Ihsan; Firman Ali Rahman (Jurnal Inovasi Pendidikan dan Sains, 2023)
This study aims to determine: 1) the effect of the Project Based Learning (PjBL) learning model on the communication skills of class VII students at MTS Darul Qur'an Bengkel. 2) the effect of the Project Based Learning (PjBL) learning model on the creative thinking skills of class VII students at MTS Darul Qur'an Workshop. This research is a Quasi-Experimental quantitative research with a Pretest-Posttest Non Equivalent Control Group design, the population in this study is all class VII consisting of 3 classes. The sample in this study was class VII B, totaling 21 people as the experimental class and class VII A, totaling 22 people as the control class. Sampling was carried out using the Cluster Random Sampling technique. Data collection techniques using tests and observation sheets. The data analysis technique used the One Way ANOVA Hypothesis Test assisted by SPSS 26. Based on the results of the analysis of the hypothesis test for students' communication skills of 0.000 <α = 0.05 and the results of hypothesis testing for students' creative thinking abilities of 0.003 <α = 0.05. So it can be concluded that there is an influence of the project based learning (PjBL) learning model on the communication skills and creative thinking of Grade VII students at MTS Darul Qur'an Bengkel.